Pemberian Seduhan Ekstrak Kunyit terhadap Tekanan Darah pada Penderita Hipertensi - Ailani, Choirida; Maliya, Arina (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effect of steeping turmeric extract on blood pressure in hypertension sufferers. This type of research is a quantitative method with a quasi experimental design approach with a non-randomized pre and post test design with control group design. The sample for this study was 30 people with a control group of 15 people and an intervention group of 15 people. This data collection technique uses purposive sampling. The measuring instrument used is the observation sheet, Blood Pressure Monitor. The analysis used was Univariate and Bivariate with the statistical test used was paired sample t-test analysis and processed using SPSS 25.0. With the results obtained, the average blood pressure before being given the turmeric extract steeping intervention was 152/87 mmHg with a standard deviation of 8,200/4,867 mmHg, while the average blood pressure after being given the turmeric extract steeping intervention was 141/80 mmHg and the standard deviation 10,025/4,320 mmHg. It was concluded that there was a difference in the effect of steeping turmeric extract on diastolic blood pressure in the intervention and control groups with a significance value of 0.002 < 0.05. Keywords: Hypertension, Turmeric Extract Infusion, Blood Pressure